2016
DOI: 10.14712/23366052.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

Forearm muscle oxygenation during sustained isometric contractions in rock climbers

Abstract: Background. Bouldering and lead climbing are divergent disciplines of the sport of rock climbing. Bouldering moves are short and powerful, whilst sport climbing is longer and require a greater degree of endurance.Aim. The aim of this study was to compare forearm muscle oxygenation during sustained isometric contraction between lead climbers (LC) and boulderers (BO).Methods. Eight BO and twelve LC completed maximal finger flexor strength test and sustained contractions to exhaustion at 60% of maximum voluntary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…x force (N)]. It is unlikely that the low percentage of MVC (40%) used in the FTI affected the results as no differences have also been reported when the contraction was performed at 60%MVC (Kodejska et al, 2015). As such it may be that the FTI is not an appropriate measure and MVC/∆FAV is a more sensitive marker for distinguishing between ability groups and disciplines within the sport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…x force (N)]. It is unlikely that the low percentage of MVC (40%) used in the FTI affected the results as no differences have also been reported when the contraction was performed at 60%MVC (Kodejska et al, 2015). As such it may be that the FTI is not an appropriate measure and MVC/∆FAV is a more sensitive marker for distinguishing between ability groups and disciplines within the sport.…”
Section: Discussionmentioning
confidence: 99%
“…Sport climbing and bouldering both rely heavily on the performance of the forearms, but are potentially divergent with respect to the dominant metabolism. Although both disciplines have substantially grown over the past two decades, the majority of the literature has focused solely on sport climbing (Kodejska, Michailov, & Balas, 2015). Sport climbing requires the individual to ascend a route which is usually between 15 m and 30 m in height taking approximately 3 -7 min to ascend; every few meters the person clips a rope to a fixing in the rock/wall to protect them against a fall.…”
Section: Introductionmentioning
confidence: 99%
“…1). Similar to the results of isometric holds in other data collections 24 two clear phases of deoxygenation can be seen and therefore the piecewise regression was set up to establish four knots. TTmin was then set at the corresponding point in time.…”
Section: Statisical Analysesmentioning
confidence: 84%
“…The hand position applied by all participants was a half crimp; the thumb was not used. A 23 mm rung depth was used for all the trails, following the procedure of a series of previous publication 17,24 . For every trial the participants were allowed to apply commercially available climbing chalk (magnesium carbonate).…”
Section: Finger-hang Testmentioning
confidence: 99%
“…Even at 60 % MVC, boulderers would have a greater reliance on local anaerobic strength compared to sport climbers and thus any increase in vessel dilation caused by NZBC may not have been as important for the performance of these individuals. This seems particularly probable given that (Baláš et al, 2016) found that, at least during continuous forearm testing, boulders and sport climbers used different metabolic pathways during their exhaustive exercise bouts at 60 % MVC, whilst achieving the same impulse (Kodejska, Michailov, & Balas, 2015). Another potential explanation may be related to the nature of the exercise involved.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%